Mobile Language Learning Innovation Inspired by Migrants - Agnes Kukulska-Hulme (Journal of Learning for Development, 2019)
Migrants arriving in a country are not always welcome. Similarly, the arrival of new technologies can be perceived as a blot on the familiar landscape of established educational practices. This paper seeks a productive synergy between migrants’ educational requirements with respect to learning the language of their host society; their valuable and unique human experiences and talents; and innovative learning designs that harness the ubiquity of smartphones and other mobile technologies. The present-day mass mobility and migration of individuals and groups of people sows the seeds of new ideas, generating novel approaches to language teaching and learning supported by personal technologies. There is a substantial body of evidence from research and practice for the effectiveness and appeal of mobile language learning in various educational settings, however, a specific focus on migrant learners is a more recent development. The paper provides an analysis of innovative mobile language learning projects and applications designed for migrants. It is argued that innovations resulting from a concern with supporting migrant learners can also benefit other mobile populations, such as students and business people, through the introduction of more adaptable ways of fostering and organizing learning.